PROFIL KEMISKINAN KABUPATEN KONAWE KEPULAUAN - Laode Samsul Barani; Ahmad Ahmad; Muhamad Armawaddin (Universitas Halu Oleo, 2019)
The aim of this study to: 1) the map actual condition of the population and poor families status Konawe Islands, 2) the map measure and indicator of the characteristics of people with poor status in Konawe islands. 3) provide information relating to the size and indicators of each region based on the characteristics of people with poor status in Konawe islands.The results showed that the populationKonawe Islands in 2014 rank of poverty is still above the average provincial and national poverty. The above conditions are mostly associated with; (1) low quality and educational services, (2) low quality and health services, (3) low employment and business field, (4) low quality and basic services of drinking water, and (5) low quality and housing and sanitation